Performance of Total Haemocyte Count and Survival Rate The Tiger Prawn Penaeus Monodon Fabricius Juvenile Rearing at High Density - Tayibu, Hartinah; La Sennung, La Paturusi; Ratnasari, Ratnasari; Hamal, Rimal; Dahlia, Dahlia; Rustam, Rustam (Aquacultura Indonesiana, 2017)
High density is one of the common consequences of intensive shrimp culture. High density can induce stress on the shrimp. Nonetheless, stress is not always harmful. In limited period, stress can trigger metabolism process and the hormonal system of the body. This study aimed to determine how high-density rearing causes stress on juvenile shrimp. The experiment consisted of three different density treatments, 60, 90 and 120 tiger prawn juveniles/m2  with two different weight groups,  3 to 10 g,  and 11 to 16g as test animals. Each treatment with 3 replications, and 2 stocks were provided for treatment A, B, and C respectively (the stock was prepared to substitute the test animals at hemolymph sampling). Total Haemocyte Count (THC) was the main parameter used as a reference in assessing the response of tiger prawn juveniles to hight density. Based on the 3 treatments densities tested, the results showed that THC of the juvenile tiger prawns reared at 3 densities increased up to 24 h observation and decreased at 36 h observation. In fact, THC of the shrimp at the highest rearing density of 120 juveniles/m2 increased, which is one of the alleged treatment of tiger prawn juveniles tried to increase the tiger  prawn's body defence. But the decline in THC was observed in the lowest rearing density of 60 shrimps/m2, in which the treatment did not cause stress on the tiger prawns  in the lower weight group of 5 to10g (treatment A). In contrast, THC of the tiger prawn  in the medium and highest rearing density (treatment B and C) drastically declined due to stress on tiger prawn juvenile and led to the tiger prawn  dead.  However, it is assumed that the tiger prawn juvenile that can adapt to the stressful condition, stress may become a stimulus that can trigger moulting, which is olso known as an indicator of growth.